Income Analysis of Palm Sugar Processing Business (Arenga saccharifera) in Wansugi Village, Kabangka District, Muna Regency - Andriani, Mimi; Gafarudin, Abdul; Sadimantara, Fahria Nadiryati (International journal of technology and education research, 2025)
This study aims to determine the amount of income from the palm sugar processing business in Wansugi Village, Kabangka District. This research was conducted in October 2024 - March 2025. The population in this study were business actors in Wansugi Village, Kabangka District, Muna Regency. To determine the sample in this study, the Census Sampling method was used for palm sugar processing business actors. This study was analyzed using quantitative descriptive analysis. The results of this study indicate that the average total income per month in palm sugar processing is IDR 1,445,000 with an average total cost per month of IDR 88,024 and an average income of palm sugar processors per month of IDR 1,257,944. With an R/C Ratio value of 1.12, it means that the palm sugar processing business in Wansugi Village, Kabangka District is feasible to be developed because the R/C Ratio value is > 1